85 Post operative complications in adult congenital heart disease. (5th June 2017) - Pick, Emma; Quirk, Jo; Birkett, Jo; Cullington, Damien; Oliver, James; Congiu, Stefano; Jaber, Osama; Doorn, Carin Van; English, Kate
Abstract : Introduction: Increasing numbers of adults with congenital heart disease (ACHD) are undergoing redo or primary surgical procedures. There is little available data relating to post-operative mortality and morbidity in this group. Methods: We examined 99 consecutive ACHD patients who underwent cardiac surgery in our institution over twelve months from April 2015. Data collected included age, body mass index (BMI), type of procedure, whether the procedure was a primary procedure or a redo, length of stay and the occurrence of any complications. Complications were classified as requiring intervention or self-limiting. Whether complications had permanent long term sequelae or not was assessed. Results: Patients were aged between 16 and 69 years. 41 patients underwent a primary procedure, and there were 58 redo operations. 19 different primary procedures were performed, and 20 patients underwent a multi-faceted procedure. 56% of patients had a BMI above the normal range. Median length of stay was 8 days, IQR 7–10, range 3–42. 68 complications occurred in 46 patients. There were 2 deaths. There were 54 complications requiring intervention, and 14 self-limiting complications. 28 patients had 1 complication, 14 patients had 2 complications and 4 patients had 3 complications. The most common complications requiring intervention were post-operative chest infection requiring oral or IV antibiotics (n=19), atrial arrhythmia requiring anti-arrhythmic therapy or cardioversion (n=7), post-operative wound infection requiring IV or oral antibiotics (n=7), and pericardial effusion requiring drainage (n=5). Self-limiting complications included 1 patient with nodal rhythm with pauses, 2 patients with an acute confusional state, 1 patient with a groin haematoma (following fem-fem bypass), 1 patient with a residual VSD following resection of double chambered right ventricle and 1 patient with gastroenteritis. Apart from the 2 deaths, there were 4 patients who had long term sequelae from their complication. 1 patient in their 60's suffered a peri-operative cerebellar stroke, 1 patient required a permanent pacemaker, and 2 patients had vocal cord palsy leading to hoarse voice. Post-operative complications increased in incidence with both increasing age and increasing BMI. (Figs 1&2) Conclusions: Increasing numbers of cardiac surgical procedures are being performed in ACHD patients because of their increasing numbers and complexity. This study demonstrates that even complex surgery can be undertaken at low mortality risk. Just under 50% of patients experience one or more peri-operative complications but the vast majority are successfully treated with no long term adverse consequences. Complications appear to increase with advancing age and BMI.